The Purpose and Importance of Static Exercises (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
One of the important benefits of isometric exercises is the efficient use of time. It takes a few minutes for the muscles to actively participate in training. At the same time, the exercises are performed in a small amount of time, and severe fatigue does not occur, as happens during regular sports training, when the muscles last for several hours. This makes it possible to make the most of the 45 minutes allotted to the physical education lesson and to influence all muscle groups of students in this short period of time.